Termination-acidity tailoring of molybdenum carbides for alkaline hydrogen evolution reaction - Zhigang Chen; Minghao Yang; Yifan Li; Wenbin Gong; Juan Wang; Tong Liu; Chunyu Zhang; Shuang Hou; Guang Yang; Hao Li; Ye Jin; Chunyan Zhang; et al. (Nature Communications)
Abstract Transition-metal carbides have been advocated as the promising alternatives to noble-metal platinum-based catalysts in electrocatalytic hydrogen evolution reaction over half a century. However, the effectiveness of transition-metal carbides catalyzing hydrogen evolution in high-pH electrolyte is severely compromised due to the lowered proton activity and intractable alkaline-leaching issue of transition-metal centers. Herein, on the basis of validation of molybdenum-carbide model-catalyst system by taking advantage of surface science techniques, Mo2C micro-size spheres terminated by Al3+ doped MoO2 layer exhibit a notable performance of alkaline hydrogen evolution with a near-zero onset-potential, a low overpotential (40 mV) at a typical current density of 10 mA/cm2, and a small Tafel slope (45 mV/dec), as well as a long-term stability for continuous hydrogen production over 200 h. Advanced morphology and spectroscopy characterizations demonstrate that the local -Al-OH-Mo- structures within Al-MoO2 terminations serve as strong Brønsted acid sites that accelerate the deprotonation kinetics in alkaline HER process. Our work paves an interesting termination-acidity-tailoring strategy to explore cost-effective catalysts towards water electrolysis and beyond.